Urotensin-II receptor contributes to the pro-inflammatory TLR4/MyD88/NF-κB/iNOS/NO pathway-mediated cardiovascular response to systemic lipopolysaccharide challenge in a septic shock model in rats: Protective effects of SB-710411 against septic shock - Ahmed-Reda Elosman, Muhammed; Senol, Sefika Pinar; Ikiz, Elif; Tunctan, Bahar (Cellular and Molecular Biology, 2025)
Urotensin (U)-II through the U-II receptor (UT) (the orphan G protein-coupled receptor; GPR14) plays an important role in the pathogenesis of many cardiovascular and renal diseases characterized by increased production of vasodilatory and pro-inflammatory mediators. This study tested the hypothesis of whether UT contributes to the pro-inflammatory TLR4/MyD88/NF-kB/iNOS/NO pathway-mediated changes in the cardiovascular response to systemic lipopolysaccharide (LPS) challenge in a rat model of septic shock. SB-710411, a UT antagonist, was used to test this hypothesis. Rats were injected with SB-710411 1 hour following an injection of saline or LPS. A tail-cuff device was used to record the mean arterial pressure and heart rate values of rats. Serum U-II and nitrite levels and U-II, GPR14, TLR4, MyD88, NF-kB, IL-1β, and iNOS mRNA expression in the cardiovascular and renal tissues were measured. Mean arterial pressure was reduced and heart rate was increased at 4 hours following LPS injection. In addition to the levels of U-II and nitrite in the sera of rats injected with LPS, the expression of U-II, GPR14, TLR4, MyD88, NF-kB, IL-1β, and iNOS was increased in the cardiovascular and renal tissues. SB-710411 at 0.01 mg/kg dose ameliorated the changes induced by LPS, excepting the increased serum nitrite level. These findings suggest that UT contributes to hypotension and tachycardia mediated by the TLR4/MyD88/NF-kB/iNOS/NO pathway, accompanied by an increase in pro-inflammatory cytokine expression in tissues related to the cardiovascular and renal systems, in response to systemic LPS challenge in rats.